2005
DOI: 10.1186/1745-9974-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cough reflex sensitivity after an inhaled antigen challenge between actively and passively sensitized guinea pigs

Abstract: Background: Late asthmatic response is observed following antigen challenge in actively, but not passively, sensitized guinea pigs. Although cough reflex sensitivity is increased after antigen challenge in actively sensitized guinea pigs, it is unknown whether the antigen-induced increase in cough reflex sensitivity develops in passively sensitized animals. The aim of this study was to compare the cough reflex sensitivity to inhaled capsaicin after an inhaled antigen challenge between actively and passively se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition, it has been shown that both the NK 1 receptor antagonist FK888 and the dual NK 1 and NK 2 peptide receptor antagonists FK224 significantly inhibited the increase in cough response to inhaled capsaicin in different types of guinea pig models of cough with allergic airway inflammation [31][32][33]. In our laboratory, we previously showed in the actively sensitized guinea pigs that the increase in the cough reflex sensitivity after an antigen challenge is correlated with increase in the SP levels in the BALF [18] and the decrease in the NEP activity in the tracheal tissue [19], which are consistent with the results in the present study. Taken together, these findings suggest that the role of peripheral SP in cough reflex sensitivity may be different between species and/or employed experimental systems, especially presence of airway inflammation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, it has been shown that both the NK 1 receptor antagonist FK888 and the dual NK 1 and NK 2 peptide receptor antagonists FK224 significantly inhibited the increase in cough response to inhaled capsaicin in different types of guinea pig models of cough with allergic airway inflammation [31][32][33]. In our laboratory, we previously showed in the actively sensitized guinea pigs that the increase in the cough reflex sensitivity after an antigen challenge is correlated with increase in the SP levels in the BALF [18] and the decrease in the NEP activity in the tracheal tissue [19], which are consistent with the results in the present study. Taken together, these findings suggest that the role of peripheral SP in cough reflex sensitivity may be different between species and/or employed experimental systems, especially presence of airway inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…Thirty minutes later, the conscious guinea pigs were challenged for 90 seconds with 10 mg/ml OA aerosol by a method described previously [6,18,19]. The animals in the NC group were not injected with diphenhydramine, but they did inhale aerosolized saline by the same method as that described for the sensitized guinea pigs.…”
Section: Antigen Challengementioning
confidence: 99%
See 1 more Smart Citation
“…Animals were administered 1 ml of a 50 mg/ml ovalbumin (Ova) in 0.9% w/v saline solution via the intraperitoneal route and 0.5 ml of the same solution into two separate subcutaneous sites (1 ml in total divided between the left and right flank). All animals were administered a single intraperitoneal dose of pyrilamine (15 mg·kg ‐1 ) at a dose volume of 1 ml·kg ‑1 approximately 30 min prior to ovalbumin challenge on Day 14 to inhibit histamine‐induced bronchospasm (Featherstone et al, 1988; Hara et al, 2005). On Day 14, animals were challenged with aerosolized ovalbumin in 0.9% w/v saline (3 mg·ml ‐1 ) or 0.9% w/v saline for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were administered 1 mL of a 50 mg/mL Ovalbumin (Ova) in 0.9% w/v saline solution via the intraperitoneal route and 0.5 mL of the same solution into 2 separate subcutaneous sites (1 mL in total divided between the left and right flank). All animals were administered a single intraperitoneal dose of pyrilamine (15 mg/kg) at a dose volume of 1 mL/kg approximately 30 min prior to ovalbumin challenge on Day 14 to inhibit histamine-induced bronchospasm (Featherstone et al, 1988;Hara et al, 2005). On Day 14 animals were challenged with aerosolised ovalbumin in 0.9% w/v saline (3 mg/mL) or 0.9% w/v saline for 15 min.…”
Section: Guinea Pig Cough Experimentsmentioning
confidence: 99%